(untitled) (Journal of Education, Humanities, and Social Research, 2025)
In the era of globalization and China’s "Culture Going Global" strategy, promoting red culture on the international stage has become a crucial means for us college students to enhance national cultural confidence and tell Chinese stories well. As a red landmark commemorating the deeds and spirits of predecessors, the Zhou-Deng Memorial Hall shoulders the mission of spreading China’s revolutionary spirit. However, when carrying out international communication, the memorial hall faces practical challenges: incomplete bilingual materials and biased cross-cultural interpretation, which seriously affect the communication effect of red culture. Therefore, optimizing bilingual guided tour services is an urgent task we students hope to address. In this study, combining the current situation of the memorial hall, we propose three-dimensional solutions: At the content level, construct a standardized bilingual lexicon. In service models, create an "online + offline" integrated system. At the resource integration level, expand international cooperation actively, use overseas social media to broaden communication, seek support from cultural and tourism projects, and introduce cutting-edge digital technologies. This study provides practical ideas for the memorial hall and other domestic red venues to improve bilingual tour services. As college students, we hope our research not only enhances the international communication effectiveness of red culture but also contributes to constructing the international discourse system of Chinese red culture. During the research, we deeply felt the significance of red culture communication and expect these suggestions to inspire the international development of red culture venues.